LA NARRATIVA PETROLERA VENEZOLANA: UNA MUESTRA DE LA VISIÓN CRÍTICA DE NUESTRA SOCIEDAD (De la Crítica, 2023)
The novels "Mene" (1936), "Casas Muertas" (1955) and "País Portátil" (1969) portray the history of oil-rich Venezuela, from its beginnings to the incomplete modernization of the country. This research aims to analyze Venezuelan oil literature as a critical reflection of society, based on Claude Duchet's socio-critical theory. The objective is to find societal reflections in these literary works, highlighting the marks and traces left by society within them. The methodological approach is documentary and descriptive, concluding that Venezuelan oil literature is the most representative expression of the reality surrounding the establishment of the oil industry in the country. The novels by authors such as Díaz Sánchez, Otero Silva, and González León express their vision of the impact of oil on the modernization of a socially backward country. Reading and dissemination of these works are recommended to foster the study of national history through oil literature.